Gwarancje proceduralne na wypadek wydalenia cudzoziemca w systemie Europejskiej konwencji praw człowieka - Mizerski, Rafał (Studia Prawa Publicznego, 2019)
The author discusses the legal basis, the cope of application, the content and the concurrence of procedural guarantees in the event of an expulsion of an alien under the European Convention. These guarantees stem from Article 1 of Protocol No. 7, Article 4 of Protocol No. 4, Articles 13 and 34 of the Convention as well as from the concepts of positive obligations and tests of legality and necessity, developed in the case law of the Strasbourg Court. Guarantees under Article 1 of Protocol No. 7 and Article 4 of Protocol No. 4 are the only ones that are applicable regardless of whether an expulsion results in the violation of an alien’s rights or the limitation of the freedoms arising from the Convention. Moreover, they do not apply to extradition proceedings, whereas the other guarantees do. However, in the context of the guarantees resulting from Article 13 of the Convention and the concepts of positive obligations as well as the tests of legality and necessity, a common standard of procedural requirements in an event of an expulsion of an alien seems to have emerged. It includes the alien’s right to information on the speciﬁ c reasons for expulsion; available remedies and a possibility of obtaining legal assistance; the right to submit arguments against expulsion; the right to be represented; the right to have the case reviewed; the right to an independent and impartial authority competent to decide in the case. In the event where an expulsion puts an alien in danger of irreversible damage to his/her rights, the person concerned should have, in addition, access to a remedy with automatic suspensive eff ect. This standard is also quite common to guarantees stemming from Articles 1 of Protocol No. 7 and Article 4 of Protocol No. 4. However, since “competent authority” under Article 1 of Protocol No. 7 need not be the authority with whom the ﬁ nal decision on expulsion rests and because it is possible to expel an alien before the exercise of his/her rights under this Article, the author is of the opinion that the latter should apply only to expulsions that do not threaten conventional rights.